Impact of the Dementia Care in Hospitals Program on acute hospital staff satisfaction - Margaret E. Murray; Anna Wong Shee; Emma West; Michelle Morvell; Meredith Theobald; Vincent Versace; Mark Yates (BMC, 2019)
Abstract Background To evaluate the impact of the Dementia Care in Hospitals Program (DCHP) on clinical and non-clinical staff job satisfaction, level of confidence and comfort in caring for patients with cognitive impairment (CI). Staff perceptions of how organisational support and hospital environment met the needs of patients with CI were also assessed. Methods The DCHP was implemented across four acute hospital sites across Australia. Clinical and non-clinical staff received training on CI screening and communication strategies for patients with CI. A staff satisfaction survey was administered pre- and post-implementation of the DCHP. Results One thousand seven hundred forty-eight staff received DCHP education and 1375 staff participated in the survey. Self-reported confidence and level of comfort in caring for patients with CI significantly improved following implementation. Staff also reported increased job satisfaction and organisational support at all hospital sites. Conclusions The DCHP implementation within an acute hospital setting was found to show an improvement in staff confidence, comfort, and job satisfaction when caring for patients with CI. This study has significant implications for the improvement of care for patients with CI as well as staff retention and job satisfaction. Further research is required to determine whether these improvements are sustained in the longer term.